Arquitetura moderna em Fortaleza (1959-1982): narrativas fotográficas. - Pardana, Marcos Nuno Mendes da Silva (2021)
The photographic representation played a fundamental role as a means of disseminating the ideas and works of modern architecture, not only at the international level, but also in Brazil, where it made an important contribution to the legitimation of this new architecture that subsidized the construction of an idea of national identity. In order to contribute to the construction of new narratives about the diffusion of modern Brazilian architecture and the understanding of its pluralism in a non-hegemonic scenario, the research focuses on a regional context. Therefore, this dissertation aims to identify the uses of photography within the scope of modern architecture produced in the city of Fortaleza between 1959 and 1982, revealing the role of the photographic image as a form of visual representation of the body of works in question and, consequently, as means of building narratives related to that production and its diffusion process. To this end, a set of theoretical references on the theme is taken as support, as well as the documentary survey of photographic collections existing in the city about the works in question and the different publications made on them using photography. The systematization of the collections collected, the identification of the narratives transmitted via photography in the context of the aforementioned architectural production and its diffusion process, as well as the analysis of the main publications made on the subject are part of the research objectives. During the period under study, as a result of the professional activity of the first wave of architects working in the city, Fortaleza experienced the construction of a body of works that was established as an expression of modern architecture adapted to the local physical, socioeconomic and cultural conditions. The heritage, historical and cultural relevance of such a legacy, as well as the realization that it is under permanent threat of destruction and mischaracterization contribute to justify the approach to the theme. In addition, the importance of giving visibility to this modern collection and of emphasizing the need for its documentation, valuation and conservation confirm the relevance of an approach to it from the angle of photography and its different uses.